Population Diversity and Role in the Socioeconomic Development of Domestic Buffaloes of Rural Areas of District Haripur, KPK Pakistan - Bibi, Saira; Khan, Muhammad Fiaz; Rehman, Aqsa (Journal of Buffalo Science, 2018)
This study conducted as a type of survey in a time period duration of 6 month that starts from the end of the march to the end of September total of the 1000 houses were visited from each of the selected villages of Haripur Pakistan along with 100 dairy farms study carried out by the questionnaires and by the direct meeting with the keepers of buffalos. Four villages were selected where the highest population of buffaloes were found in Syria maira. The farm buffalos were kept mostly for the purpose of selling the milk Results showed that the most of the areas the buffalo keeping is for the purpose of selling the milk wile in other where the selling rate is not found they keep them for their own food and milk purposes. It facilitate their economic status to rise as a part time job. Government should take steps to rise there stander.